2022
DOI: 10.23887/jear.v6i2.45816
|View full text |Cite
|
Sign up to set email alerts
|

Model Pembelajaran Problem Based Instruction untuk Meningkatkan Hasil Belajar Tematik pada Siswa Kelas III SD

Abstract: Pelaksanaan pembelajaran yang menyajikan mata pelajaran secara terpisah akan menyebabkan kurang berkembangnya kemampuan anak untuk berpikir holistik dan membuat kesulitan bagi peserta didik. Penelitian ini bertujuan meningkatkan hasil belajar tematik melalui penerapan model pembelajaran Problem Based Instruction (PBI) pada siswa kelas III SD. Jenis penelitian adalah penelitian tindakan kelas yang melibatkan siswa kelas III yang berjumlah 29 orang siswa. Pengumpulan data hasil belajar siswa dikumpulkan dengan t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…This is different with previous research which found that at the discuss stage, students discuss to reach an agreement with all group members (Sukmawati et al, 2021). However, the findings of this research are similar with the research by Hartina et al (2022) that group discussions have not divided tasks well. The reasons are the students have yet to conclude the different opinions of answers even though the essence is the same, discussions activities are also dominated by one of the group members.…”
Section: Create Collaborationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This is different with previous research which found that at the discuss stage, students discuss to reach an agreement with all group members (Sukmawati et al, 2021). However, the findings of this research are similar with the research by Hartina et al (2022) that group discussions have not divided tasks well. The reasons are the students have yet to conclude the different opinions of answers even though the essence is the same, discussions activities are also dominated by one of the group members.…”
Section: Create Collaborationcontrasting
confidence: 99%
“…Apart from that, another study with the title "The Impact of Problem Based Learning on Improving Collaboration Skills in Thematic Learning" by Hartina et al (2022). This research found that student collaboration in cycle I and cycle II experienced an average increase of 5.45 points.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Post-intervention (posttest), applying the Socioscientific Issues-based RICOSRE model, the experimental group achieved a 'highly collaborative' rating with an average score of 80.21, while the control group was categorized as 'collaborative' with a score of 72.37. These results demonstrate the effectiveness of the Socioscientific Issues-informed RICOSRE model in significantly enhancing students' collaborative abilities during the research period (Hartina et al, 2022). Table 8 describes the process carried out by researchers during the research process.…”
Section: Analysis Of Student Collaboration Abilitymentioning
confidence: 66%
“…Menurut (Hartina et al, 2022) terjadi peningkatan dari skilus 1 dan siklus 2 kemampuan berkolaborasi peserta didik sebesar 5,45 % menggunakan model Problem based learning. Beberapa penelitian juga menyebutkan bahwa pembelajaran berdiferensiasi mampu meningkatkan kemampuan abad 21 yaitu kemampuan berkolaborasi pada peserta didik.…”
Section: Pendahuluanunclassified